Development of Curriculum and Learning System in Pondok Pesantren. (A Case Study at Pesantren Al Falah Dago Bandung) - Koko Adya Winata; Andewi Suhartini; Nurwadjah Ahmad (RIRAI Publisher, 2021)
This study aims to determine the development of the curriculum and learning system implemented in the Al Falah Dago Islamic boarding school in Bandung. This research uses a qualitative approach in the form of a case study. Data were collected using observation, interview, field observation, and document study. The validity of the data was obtained utilizing triangulation and supplemented with referential adequacy. Data analysis was performed by data reduction, data presentation, and verification. The results of the research show that; 1) Pondok Pesantren Al Falah Dago, Bandung City still maintains the old pattern both in terms of curriculum and learning system, 2) learning activities are carried out using yellow books or classical books, 3) the learning system uses traditional methods such as sorogan, bandongan, memorization and bahsu al-Masa'il, as well as memorizing and modern uses such as group learning and discussions between students.